Impact of nitrogen fertilization on the forage characteristics and beef calf performance on native pasture overseeded with ryegrass - Brambilla,Daniel Martins (2012)
The overseeding of ryegrass (Lolium multiflorum Lam) on sub-tropical native pastures increases the availability and quality of forage in the cold season. However, soil chemical amendment and nitrogen use can affect the floristic composition, with consequences to the primary and secondary production. In a randomized complete block design with three replications, the effect of nitrogen fertilization (40, 90 and 140 kg/ha of nitrogen) on native pasture overseeded with ryegrass in two consecutive years was assessed regarding production and composition of pasture and performance of beef calves. In both years, the forage accumulation rate and forage production responded linearly to the increase in nitrogen rates as a result of increased participation of ryegrass. The lower efficiency of responses in 2008 was due to the increased participation of dead material and the reduction of ryegrass in the forage sward. In 2007 there was an increasing substitution of the participation of native grasses by ryegrass with increasing nitrogen rates. Native legumes and other species were almost not affected by nitrogen fertilization. The average daily weight gain of the animals responded linearly to nitrogen rates in 2007, and quadratically in 2008. The stocking rate and gain per hectare increased linearly in both years, with greater responses in 2007. The production and composition of forage and livestock production are improved by the use of nitrogen, but the efficiency of responses can be affected by sowing date and nitrogen fertilization.